Bio- and mineral acid leaching of rare earth elements from synthetic phosphogypsum. (May 2019) - Antonick, Paul J.; Hu, Zhichao; Fujita, Yoshiko; Reed, David W.; Das, Gaurav; Wu, Lili; Shivaramaiah, Radha; Kim, Paul; Eslamimanesh, Ali; Lencka, Malgorzata M.; Jiao, Yongqin; Anderko, Andrzej; et al.
Graphical abstract: Highlights: Comparison of lixiviants for leaching rare earth elements from synthetic phosphogypsum. Leaching efficiency: H2 SO4 > Biolixiviant > Gluconic Acid > H3 PO4 for Ce, Nd, Sm, Eu, and Yb. Thermodynamic simulations consistent with experimental results. Abstract: Leaching of six individual rare earth (yttrium, cerium, neodymium, samarium, europium, and ytterbium) doped synthetic phosphogypsum samples using a suite of lixiviants was conducted. The lixiviants chosen for this study were phosphoric acid, sulfuric acid, gluconic acid, and a "biolixiviant" consisting of spent medium containing organic acids from the growth of the bacterium Gluconobacter oxydans on glucose. The biolixiviant had a pH of 2.1 and the dominant organic acid was determined to be gluconic acid, present at a concentration of 220 mM. The leaching behaviors of the studied lixiviants were compared and rationalized by thermodynamic simulations. The results suggest that at equivalent molar concentrations of 220 mM the biolixiviant was more efficient at rare earth element (REE) extraction than gluconic acid and phosphoric acid but less efficient than sulfuric acid. Unlike the organic acids, at pH 2.1 the mineral acids failed to extract REE, likely due to different complexation and kinetic effects.